Analysis of the Interactions Between Humans and Crocodiles in Costa Rica - Porras Murillo, Laura Patricia (2020)
The habitat of crocodiles (Crocodylus acutus) and caimans (Caiman crocodilus) has been subjected to pressure due to human expansion. Habitat reduction, coupled with the simultaneous growth of the crocodile population, increases the number of interactions between crocodiles and humans. There is currently no official and systematized interactions database, but it is necessary to know the magnitude and nature of the interactions and establish management measures. The objective of the work was to systematize and evaluate the interactions between crocodiles and humans in Costa Rica. Historical information was collected from several sources. A total of 99 records, dated between 1990–2017, were found from press reports and the Integrated System for Processing Environmental Complaints of the Ministry of Environment and Energy (SITADA). The Fire Department recorded 123 events in 2017. All Fire Department records corresponded to encounters or sightings. Of the SITADA incident records, 35.4% were non-fatal, 27.3% were fatal, 21.2% were encounters and sightings, and the remaining 16.1% were miscellaneous situations. Most interactions occurred during the day, a fact potentially explained by human behavior of being in bodies of water or on adjacent shoreline while the sun is out. Most interactions occurred in the Central Pacific, followed by the Caribbean and then the South Pacific. The information available is brief but allows to establish management measures. The country needs to create a national database of interactions and to encourage individuals to report their interactions. Further research should continue to analyze the data for trends with the goal of building recommendations to prevent an increase in negative interactions.